1. Dane są sumy algebraiczne - A: 2x - 3y , B: 2y - 3x , C: 2x+3y. Oblicz.

A - B =

B - A =

C - A =

B - (A + C) =

A - (B - C) =

2. Uzupełnij równość wpisując odpowiednie jednomiany.

a) 4a ( 5b - .... ) = .... - 8a²

b) ⅓t²( .... + ½t³ ) = t² + ....

c) .... (5a² - 0,2) = .... - a

d) (.... + 3xy²) : 6 = 2x²y + ....

e) (4y - 6x) : .... = -2y + 3x

f) (½t⁴ - ⅗w⁴) : .... = .... -⅕w⁴

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-29T16:53:48+01:00
1.
2x - 3y-(2y - 3x)=2x-3y-2y+3x=5x-5y
2y - 3x-(2x - 3y)=2y-3x-2x+3y=5y-5x
2x + 3y-(2x - 3y)= 2x+3y-2x+3y=6y
2y - 3x-(2x - 3y+2x + 3y)=2y-3x-4x=2y-7x
2x - 3y-(2x + 3y-(2y - 3x))=2x-3y-(2x+3y-2y+3x)=2x-3y-5x-y=-3x-4y
2.
4a(5b-2a)=20ab-8a2
⅓t²(3+½t³)=t²+1/6t5
5a(5a²-0,2)=25a³-a
(12x²y+3xy²) : 6= 2x²y+½xy²
(4y-6x) :(-2)=-2y+3x
(½t⁴ - ⅗w⁴) : 3 = 1/6t⁴ -⅕w⁴
30 4 30
2009-11-29T17:22:03+01:00
1) A-B=2x-3y-2y-3x=-x-5y
B-A=2y-3x-2x-3y=-x-5x
C-A=2x+3y-2x-3y=0
B - (A + C) =2y - 3x-( 2x - 3y +2x+3y)=2y-3x-4x=2y-7x
A - (B - C) =2x - 3y-( 2y - 3x- 2x+3y)=2x-3y-5y-5x=-3x-8y

2)
a) 4a ( 5b - .2a... ) = .20ab... - 8a²
b) ⅓t²( 3 + ½t³ ) = t² + 1/6t⁵
c) 5a (5a² - 0,2) = 25a³ - a
d) 12xy(2x+ 3xy²) : 6 = 2x²y + 6x²y³
e) (4y - 6x) : (-2) = -2y + 3x
f) (½t⁴ - ⅗w⁴) :3 = 1/6t -⅕w⁴
13 4 13